PENERAPAN MEDIA MANIK – MANIK UNTUK MENINGKATKAN HASIL BELAJAR BERHITUNG BILANGAN BULAT PADA SISWA KELAS IV MI MIFTAHUL HUDA GEMPOL KURUNG MENGANTI – GRESIK. - Yuliana, Leni; Pratiwi, Desi Eka; Saputra, Maulana Rafi Rulis; Sari, Miranda Noerdiana (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
The purpose of this research is to determine the learning outcomes of integer arithmetic using bead media among fourth-grade students at MI Miftahul Huda Gempol Kurung Menganti-Gresik. This study is classified as Classroom Action Research (CAR), with 26 fourth-grade students as the subjects. Data collection techniques used in this research include tests and observations. The collected data were analyzed qualitatively for observational data and quantitatively for test data, and the research was conducted over two cycles. Based on the research results, it was found that in the pre-cycle, cycle I, and cycle II, the use of bead media improved the learning outcomes of fourth-grade students on the topics of addition and subtraction of integers. The teacher's activity level increased from 72% in cycle I to 85.33% in cycle II. The percentage of student activity rose from 73.33% in cycle I to 83.33% in cycle II. Additionally, student learning outcomes improved from 42.30% in the pre-cycle to 69.23% in cycle I, and further increased to 96.15% in cycle II.